Obtusifolin, an Anthraquinone Extracted from Senna obtusifolia (L.) H.S.Irwin & Barneby, Reduces Inflammation in a Mouse Osteoarthritis Model - Nam, Jiho; Seol, Dong-Won; Lee, Choong-Gu; Wee, Gabbine; Yang, Siyoung; Pan, Cheol-Ho (MDPI, 2021)
Osteoarthritis (OA) is an age-related degenerative disease that causes cartilage dysfunction and inflammation. Obtusifolin, an anthraquinone extracted from Senna obtusifolia (L.) H.S.Irwin & Barneby seeds, has anti-inflammatory functions; it could be used as a drug component to relieve OA symptoms. In this study, we investigated the effects of obtusifolin on OA inflammation. In vitro, interleukin (IL)-1 beta (1 ng/mL)-treated mouse chondrocytes were co-treated with obtusifolin at different concentrations. The expression of matrix metalloproteinase (Mmp) 3, Mmp13, cyclooxygenase 2 (Cox2), and signaling proteins was measured by polymerase chain reaction and Western blotting; collagenase activity and the PGE(2) level were also determined. In vivo, OA-induced C57BL/6 mice were administered obtusifolin, and their cartilage was stained with Safranin O to observe damage. Obtusifolin inhibited Mmp3, Mmp13, and Cox2 expression to levels similar to or more than those after treatment with celecoxib. Additionally, obtusifolin decreased collagenase activity and the PGE(2) level. Furthermore, obtusifolin regulated OA via the NF-kappa B signaling pathway. In surgically induced OA mouse models, the cartilage destruction decreased when obtusifolin was administered orally. Taken together, our results show that obtusifolin effectively reduces cartilage damage via the regulation of MMPs and Cox2 expression. Hence, we suggest that obtusifolin could be a component of another OA symptom reliever.